Feasibility of Management of a Green Campus Photovoltaic Solar Power Plant National Institute of Technology Malang: Literature Review - Rijal Asnawi; Antariksa; Sukir Maryanto; Aminudin Afandhi; Kartiko Adi Widodo (Jurnal Pembangunan dan Alam Lestari)
The research aims to analyze the feasibility of managing a green campus photovoltaic solar power plant at the National Institute of Technology Malang. The method used is a literature review study. This method involves searching, selecting, and analyzing articles, books, journals, and other literature sources relevant to this research topic. The research results show that the National Institute of Technology (ITN-Malang) photovoltaic solar power plant (Pembangkit Listrik Tenaga Surya /PLTS) has fulfilled the energy efficiency aspect, an indicator of a green campus. Apart from that, the research results reveal that the feasibility of managing the National Institute of Technology (ITN-Malang) photovoltaic solar power plant (PLTS) from a green campus perspective considers environmental, economic, and social aspects. These three aspects have met the standards for the feasibility of managing a solar photovoltaic power plant at a university that meets green building criteria, including energy conservation, energy efficiency, and renewable energy. However, further studies are still needed related to environmental aspects, especially the use of land in the solar photovoltaic power plant area and the handling, development, and management of solar panel waste.